Financial development and economic growth nexus: another look at the panel evidence from different geographical regions - Eng, Yoke Kee; Habibullah, Muzafar Shah (LLC “СPС “Business Perspectives”, 2011)
This paper re-examines the causality issue on financial development and economic growth from a panel data perspectives using the system generalized method of moments (GMM) technique developed by Arellano and Bover (1995), and Blundell and Bond (1998). Focusing on developing countries in four main geography regions (Africa, Asia, Europe and Western Hemisphere), the main finding of the results reveals that although there exist evidence supporting the other views including the “demand following” as well as non-causal relation between the economic growth and the financial deepening, these supports are not as strong as the “supply leading” hypothesis.